Classification of bifid mandibular canals using cone beam computed tomography - Gisele Maria Correr; Daiana Iwanko; Denise Piotto Leonardi; Lucienne Miranda Ulbrich; Melissa Rodrigues de Araujo; Tatiana Miranda Deliberador (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The objective of this study was to classify the morphology of bifid mandibular canals and to evaluate their relationship with the roots of third molars, using cone beam computed tomography (CBCT) scans. The CBCT scans of 75 patients were analyzed and the bifurcations were classified according to Langlais et al. (1985). The relationship of bifurcation and third molars was established according to the following classification: class A - uninvolved, class B - close relationship, class C - intimate relationship and class D - absence of third molars. Data were submitted to descriptive statistics, and the results indicated that the patients' mean age was 48.2 (± 13.2) years. Unilateral bifurcation (Type 1) was the most frequent type (72.6%), followed by unilateral Type 2 (19.3%). Class D was the most frequent (57.33%), followed by class C (21.33%), class B (13.33%) and class A (8%). It could be concluded that most cases presented unilateral bifid mandibular canals extending to the third molar or adjacent regions, and when present, the roots seemed to be a continuation of the bifid mandibular canal